Art educators' professional learning: reflecting together to consider ontologies of quality in our praxis. Issue 5 (4th July 2022) - Selkrig, Mark; Wright, Susan; Hannigan, Shelley; Burke, Geraldine; Grenfell, Janette
ABSTRACT: Opportunities to interrogate praxis through professional learning and reflection is common for school teachers but is not straightforward or as frequently practised by tertiary educators, particularly from across different universities. In this article, the authors who are arts educators from various universities explore a framework that focuses on 'quality' visual art education. The aim was to ascertain if an ontology could be enacted to inform our collective knowledges about quality in arts education across our different contexts. Through collaborative self-study and the application of practice architectures common issues in higher education teaching are discussed. Cases are shared from critical examinations of our practices, that also foreground, interrogate and enrich our collective understandings in the practice field. A proposed model is provided illustrating how the intersection of dialogic discourse with art educational ontology, can promote insightful praxis, which is applicable to not only art education, but a range of disciplines.